Apoyo en la supervisión de la obra para la Empresa Luis Castiblanco (2023)
This internship was carried out for the company LUIS CASTIBLANCO supporting the supervision of the construction of the Casa Blanca Texaco service station in the municipality of Nobsa-Boyacá, focusing on its commercial area, which is designed with a 3-story building; This was developed under the qualitative and quantitative method, since results were obtained by own opinion and at the same time by statistics and formulas for the measurement of materials and for the analysis of results, in which the monitoring and supervision of the work is carried out, leading to correctly carry out the activities described in different logs such as: Installation of metal deck, electrowelded mesh, installation of hydraulics and sanitary, casting of plate, masonry and plastering of walls, complying with established delivery times, material used; following the guidelines of the structural system proposed for the work, complying with the safety and health standards at work and established requirements in order to guarantee the correct development of the project work.